Partial acquisition of stemness properties in tumorspheres obtained from interleukin-8-treated MCF-7 cells - Natalia Ospina-Muñoz; Jean-Paul Vernot (Tumor Biology)
The interleukin-8 is an important regulator of the tumor microenvironment, promoting the epithelial–mesenchymal transition and the acquisition of stem-like cell properties in cancer cells. The tumorsphere-formation assay has been used for the identification of cancer stem cell. Interleukin-8 induces the formation of larger tumorspheres in Michigan Cancer Foundation-7 (MCF-7) cells, suggesting cancer stem cell enrichment. In this work, we aimed to study the phenotypic and functional characteristics of the cells present within the tumorspheres of MCF-7 cells previously treated with interleukin-8. MCF-7 cells treated for 5 days or not with this cytokine were further cultivated in ultralow attachment plates for another 5 days to allow tumorspheres formation. We showed that the enhanced sphere formation by MCF-7 cells was not a consequence of higher cell proliferation by interleukin-8 stimulation. Despite maintaining an epithelial–mesenchymal transition phenotype with the presence of epithelial and mesenchymal markers, basic stemness properties were impaired in tumorspheres and in those treated with interleukin-8, while others were increased. Self-renewal capacity was increased in interleukin-8-treated cells only in the first generation of tumorspheres but was not sustained in consecutive assays. Accordingly, self-renewal and reprogramming gene expression, differentiation capacity to adipocytes, and clonogenicity were also impaired. We showed also that tumorspheres were enriched in differentiated luminal cells (EpCAM+/CD49f−). Nevertheless, cells were more quiescent and maintain a partial epithelial–mesenchymal transition, consistent with their increased resistance to Paclitaxel and Doxorubicin. They also presented higher migration and interleukin-8-directed invasion. Therefore, the breast cancer cell line MCF-7, having a low stemness index, might partially acquire some stem-like cell attributes after interleukin-8 stimulation, increasing its aggressiveness.